Kerjasama Regional dalam Dinamika Global: Efektivitas Rezim APEC di Tengah Perang Dagang AS-Tiongkok 2018-2020 - Umam, Azyumardi mumtazul (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
This study evaluates the effectiveness of the APEC regime during the 2018-2020 US-China trade war, focusing on APEC's capacity to address tensions using Arild Underdal's regime effectiveness theory. The aim is to provide recommendations to enhance APEC's role in managing global trade conflicts using qualitative, descriptive-analytical methods using Underdal's framework, examining dependent, independent, and intervention variables. Secondary data from credible books, journals, and articles form the basis of the analysis. APEC is struggling with structural issues, geopolitical competition, and implementation challenges. Despite the declaration, national interests dominate, limiting cohesive and impactful policies. APEC needs stronger coordination, institutional mechanisms, and inclusive leadership to enhance its effectiveness in mitigating trade conflicts. Keywords: APEC, Regime Effectiveness, US-China Trade War